2007
DOI: 10.1253/circj.71.348
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma Plasminogen Activator Inhibitor Type-1 is an Independent Predictor of Coronary Microvascular Dysfunction in Hypertension

Abstract: Background Elevated plasma plasminogen activator inhibitor-1 (PAI-1) is related to cardiovascular events, but its role in subclinical coronary microvascular dysfunction remains unknown. Thus, in the present study it was investigated whether elevated plasma PAI-1 activity is associated with coronary microvascular dysfunction in hypertensive patients. Methods and ResultsThirty patients with untreated essential hypertension and 10 age-matched healthy controls were studied prospectively. Myocardial blood flow (MBF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…In humans, elevation of PAI-1 levels occurs in several thrombotic conditions in atherosclerotic patients and aged subjects. [27][28][29][30][31] These results are consistent with our findings in the present aged subjects, but not in the young subjects. The acute reflex of the SNS during LBNP in the young subjects appeared to decrease PAI-1 activity or change it slightly, which might contribute to the defense mechanism against hypercoagulation in the central hypovolemic state.…”
Section: Discussionsupporting
confidence: 92%
“…In humans, elevation of PAI-1 levels occurs in several thrombotic conditions in atherosclerotic patients and aged subjects. [27][28][29][30][31] These results are consistent with our findings in the present aged subjects, but not in the young subjects. The acute reflex of the SNS during LBNP in the young subjects appeared to decrease PAI-1 activity or change it slightly, which might contribute to the defense mechanism against hypercoagulation in the central hypovolemic state.…”
Section: Discussionsupporting
confidence: 92%
“…10 Prothrombin F1þ2 constitutes an important marker in vivo of thrombin generation, with potential value to discriminate individuals at risk of developing thrombosis. 11,12 In the same way, high levels of plasminogen activator inhibitor type 1 (PAI-1) are described in diverse thromboembolic states, as in coronary artery disease (CAD), in MI, [13][14][15] and in PAD. 16 In individuals who had suffered MI, fibrinolytic activity is diminished because of increased PAI-1 activity.…”
Section: Introductionmentioning
confidence: 98%
“…An increase in plasma PAI-1 concentration is associated with recurrent coronary events in the survivors of acute myocardial infarction (AMI). Elevated PAI-1 activity is associated with coronary microvascular dysfunction 1) . Although PAI-1-deficient mice exhibit no apparent abnormalities, Iwaki et al previously reported that PAI-1 deficiency in humans can cause a severe bleeding tendency and impairment of wound healing 2) , suggesting an important role of PAI-1 in thrombosis and hemostasis in humans.…”
Section: See Article Vol 23: 557-566mentioning
confidence: 99%